Simultaneous ORIF for bilateral comminuted proximal humerus fractures: Case report in an elderly patient. (2019) - Maalouly, Joseph; Aouad, Dany; Dib, Nabil; Tawk, Antonios; El Rassi, Georges
Highlights: Rare case of traumatic bilateral proximal humerus fractures. Simultaneous bilateral open reduction and internal fixation showed good recovery. Post op care is of great importance for patient recovery and return to daily activities. Abstract: Introduction: Bilateral proximal humerus fractures are rather rare and occur due to high energetic traumas in young patients and even low energetic traumas in older patients having osteoporosis. Open reduction and internal fixation (ORIF) is the most popular treatment for this type of fracture while other types of treatment such as arthroplasty or conservative treatment are also, but less commonly used. Presentation of case: This report presents the case of an 80 years old female patient with bilateral proximal humerus fractures and a history of hypothyroidism. The patient was treated with simultaneous open reduction and internal fixation and presented a normal and full-range motion in both shoulders after follow-up. Discussion: Frequency of proximal humerus fractures has increased with the increase in life expectancy. Osteoporotic people are at higher risk. Around five percent of all extremity fractures are humerus proximal end fractures for people below 40 years old and 76 % for cases of people over 40 years old, with females being more susceptible. ORIF is the treatment of choice for such fractures. Replacement arthroplasty, minimally invasive techniques and conservative management are other options depending on fracture characteristics. Conclusion: This is an interesting rare case of simultaneous bilateral proximal humerus fractures in an elderly female patient, treated operatively with satisfactory results on follow up.